Knowledge Sharing Activities In The Organization Of Regional Supreme Product Manager - Setia, Bayu Indra; Hadiyat, Yana Rochdiana; Minaryanti, Annisa Adha (TRIKONOMIKA, 2018)
The purpose of this study is to obtain empirical evidence of knowledge sharing activities in the organization of regional supreme product manager, as well as looking for factors that influenced it. The research method used was qualitative descriptive at sub-districts in Bandung, with sample of agencies, entrepreneurs, and related institutions. The ability to transform knowledge from supreme product managers and agencies to managers of products that had not become a supreme was yet optimal. It is because of the area that was not possible and its supreme product managers who did not want to share their knowledge to another products managers that had not become supreme because they fear of being competed. Nevertheless, government agencies had always understood the need for other knowledge to facilitate routine improvements of product managers that had not become supreme, such as supreme product standardization training, and requirements that must be met to become supreme product.